2022
DOI: 10.1609/aaai.v36i4.20306
|View full text |Cite
|
Sign up to set email alerts
|

How to Find a Good Explanation for Clustering?

Abstract: k-means and k-median clustering are powerful unsupervised machine learning techniques. However, due to complicated dependences on all the features, it is challenging to interpret the resulting cluster assignments. Moshkovitz, Dasgupta, Rashtchian, and Frost proposed an elegant model of explainable k-means and k-median clustering in ICML 2020. In this model, a decision tree with k leaves provides a straightforward characterization of the data set into clusters. We study two natural algorithmic questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Then, we show that analogous results hold for both the k-median and k-centers cost functions. Our results for both the k-means and k-medians are stronger than the NP-Hardness result established recently by [9] and they formally help to justify the quest for approximation algorithms and/or heuristics for these cost functions.…”
Section: Our Contributionscontrasting
confidence: 52%
See 2 more Smart Citations
“…Then, we show that analogous results hold for both the k-median and k-centers cost functions. Our results for both the k-means and k-medians are stronger than the NP-Hardness result established recently by [9] and they formally help to justify the quest for approximation algorithms and/or heuristics for these cost functions.…”
Section: Our Contributionscontrasting
confidence: 52%
“…The computational complexity of building explainable clustering via decision trees for both the k-means and the k-medians problems is studied in [9]. It is shown that both problems admit polynomial time algorithms when either k or d is constant and they are NP-Complete for arbitrary k and d. In addition, they show that an optimal explainable clustering cannot be found in f (k)•|X | o(k) time for any computable function f (), unless Exponential Time Hypothesis (ETH) fails.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Feldmann and Marx (2020) studied parameterized algorithms and complexity of k-Center clustering on networks for various structural parameters of the network. A number of recent works studied parameterized algorithms for clustering with size constraints on the clusters, among others with k-Median as the optimization objective (Cohen-Addad and Li 2019; Bandyapadhyay, Fomin, and Simonov 2021). It is worth to note that all of the results on k-Center/k-Median mentioned above offer little insight in our setting, as they heavily exploit small number of clusters.…”
Section: Croaggregation (Hereinafter Cnma)mentioning
confidence: 99%
“…More formally, we assume that the clustering is explained using decision trees, a problem that has attracted significant interest lately under the name of explainable clustering (Moshkovitz et al 2020;Makarychev and Shan 2021;Gamlath et al 2021;Bandyapadhyay et al 2022). We consider smaller decision trees (i.e., they have fewer nodes) to be more explainable as they are easier to read (Lipton 2018).…”
Section: Introductionmentioning
confidence: 99%